Potential of multimedia resources for English vocabulary improvement - Salazar Calderón, Edison Hernán; Macías Silva, Evelyn Carolina; Aquino Rojas, Marco Antonio; Vásquez Rodríguez, Edson Isaac (Revista de Ciencias Sociales, 2023)
Vocabulary is a fundamental component of learning and mastering the English language. Multimedia resources can be used to help students learn and practice their vocabulary. With the help of multimedia resources, students can access visual and audio aids that enable them to better understand words and their meanings. This research aims to analyze the potential of multimedia resources to improve English vocabulary, specifically to support students with vocabulary learning when studying English as a second language. This research is descriptive documentary, based on the search, retrieval, critical analysis and interpretation of secondary data, a qualitative approach was used to evaluate the effectiveness of multimedia. The literature review shows that such resources are optimal for vocabulary acquisition and motivate students, who tend to have a favorable opinion of their use in the educational environment. It is concluded that research has shown that the use of multimedia is advantageous for students and most of the studies reviewed consider that students use these multimedia resources to expand their vocabulary.